Risk Factors for Hypertension Incidence in the Riverbank Communities of Banjarmasin City - Farida Heriyani; Siti Habibah Zein; Widya Nursantari; Nika Sterina Skripsiana (Fakultas Kedokteran Universitas Lambung Mangkurat, 2025)
Hypertension is a serious medical condition and a leading cause of death worldwide, including in Indonesia. South Kalimantan ranks second for the highest number of hypertension cases Indonesia. Banjarmasin City, particularly its riverbank areas, has unique environmental and socioeconomic conditions that may influence the health status of its residents, including the incidence of hypertension. This study aims to describe the risk factors for hypertension incidence among communities living along the riverbanks of Banjarmasin City, South Kalimantan. This descriptive study involved 70 respondents diagnosed with hypertension from three areas of Puskesmas (Community Health Center) in Banjarmasin City. The results of the study showed several risk factors for hypertension found among the respondents, including age ≥ 40 years (84.29%), female gender (65.71%), Banjar ethnicity (71.43%), high school or equivalent education level (64.29%), knowledge (50%), unemployed status (62.86%), family history of hypertension (68.57%), high salt consumption habits (65.71%), insufficient rest (42.86%), smoking habits (22.86%), low physical activity (62.86%), and obesity (31.43%). These findings indicate that the majority of respondents possessed a combination of both modifiable and non-modifiable risk factors. Therefore, early detection for non-modifiable risk groups and targeted health education and promotion efforts are essential to encourage lifestyle changes and prevent hypertension in the riverbank communities of Banjarmasin City.